2019
DOI: 10.1101/649764
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted brain tumor radiotherapy using an Auger emitter

Abstract: One Sentence Summary:A novel PARP1-targeted Auger radiotherapeutic shows translational potential as a theranostic tool for imaging and killing cancer cells, resulting in tumor delineation and prolonged survival in a glioblastoma model. AbstractGlioblastoma multiforme is a highly aggressive form of brain cancer whose location, tendency to infiltrate healthy surrounding tissue, and heterogeneity significantly limit survival, with scant progress having been made in recent decades. 123 I-MAPi (Iodine-123 Meitner-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…A recently published study demonstrated promising results using a theragnostic Auger emitting PARP inhibitor (123I-MAPi) in a preclinical model. Taking advantage of the physical properties of Auger emission, dependent on the proximity of the electron emitter to the DNA to cause cellular damage, along with the biological expression of PARP1/2, much higher in cancer when compared to normal cells, it was possible to achieve lethal cancer doses with limited normal tissue toxicity ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study demonstrated promising results using a theragnostic Auger emitting PARP inhibitor (123I-MAPi) in a preclinical model. Taking advantage of the physical properties of Auger emission, dependent on the proximity of the electron emitter to the DNA to cause cellular damage, along with the biological expression of PARP1/2, much higher in cancer when compared to normal cells, it was possible to achieve lethal cancer doses with limited normal tissue toxicity ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several PARP inhibitors have also been labeled with therapeutic isotopes (Salinas et al, 2015;Jannetti et al, 2018;Reilly et al, 2018;Makvandi et al, 2019;Pirovano et al, 2019). The pharmacokinetic profiles of several iodinated PARP inhibitors based on olaparib were explored in human glioblastoma models in vitro and in vivo.…”
Section: Parpi Radiotherapeuticsmentioning
confidence: 99%
“…The rucaparib scaffold was also leveraged in the design and synthesis of alpha-and auger-emitting radiotherapeutics using copper-catalyzed halogenation of boronic esters (Reilly et al, 2018;Makvandi et al, 2019). The efficacy of PARP-targeted radiotherapeutics was first published in subcutaneous mouse models of glioblastoma, and later in orthotopic models of human glioblastoma (Jannetti et al, 2018;Pirovano et al, 2019). Intratumoral injections were implemented to mimic Convection Enhanced Delivery (CED).…”
Section: Parpi Radiotherapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radioiodinated UdRs are effective as they covalently bind to DNA hence the Auger emissions are in perfect range to damage the DNA of the cancer cells. 123 I‐labelled Meitner ‐ Auger PARP1 (Figure 12) is an inhibitor used to treat a form of brain cancer known as Glioblastoma multiforme 114 . Not only can the gamma ray emission treat this type of cancer utilising Auger electrons but can also be used to image the patient and track therapeutic response and tumour advancement.…”
Section: Introductionmentioning
confidence: 99%